Determining the KPIs of the German engineering industry based on the evaluation of contemporary business models - Kostin Konstantin B. (University of Novi Sad - Faculty of Economics, Subotica, 2021)
This study determines the correlation between industry-specific success patterns of the German engineering industry and the business models applied within. In order to identify this correlation, the following objectives are addressed within the framework of this paper: (1) identification and description of business models used by the German engineering industry; (2) analysis of industry-specific success patterns of the German engineering industry by the usage of Key Performance Indicators (KPIs); and (3) determination of correlation between the KPIs and the effectiveness of the business models of the German engineering industry These objectives are mainly achieved by literature research and expert surveys. The findings highlight the KPIs (overall 41) that are relevant for the respective business models. This enables a better understanding of the interrelationships of the business model, in order to derive relevant conclusions. The paper contributes to the literature as it advances this field of research in Germany, and it is one of the first studies to examine the relationship between business models and industry-specific success patterns with relevant KPIs.